Persepsi Masyarakat Mengenai Kesetaraan Gender dalam Keluarga di Desa Tangkit Kabupaten Muaro Jambi - Mahmuda, Indah; Rahmah Ramadhoni, Sri; Yanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe community perceptions of gender equality within families in Tangkit Village, Muaro Jambi Regency. The study employed a descriptive qualitative approach with three informants selected through purposive sampling. Data were collected through observation, interviews, and documentation, then analyzed using data reduction, data presentation, and conclusion-drawing techniques. The results indicate that the community of Tangkit Village generally hold positive perceptions regarding gender equality. The community supports women’s rights to education, employment, and participation in family decision-making. However, the division of roles within the family still tends to follow traditional patterns that place men as the primary breadwinners and women as the primary caregivers for domestic work. Additionally, the influence of patriarchal values remains evident in several aspects of family life. This study concludes that the community’s perceptions of gender equality have led to more equitable relationships, although practices are still influenced by traditional gender norms and constructs.